Squaring the Circle: A Critique of the Islamisation of the Human Sciences Project - Hussain, Feryad; Bouzenita, Anke Iman (Islamic Studies, 2011)
The Islamisation ofHuman SciencesProject was proposed in the late 20th century as a response to the educational dilemma faced by the Muslims worldwide. The predominance of non-Islamic models of thought and academic contents was addressed by a number of models with varying emphases on the level of integration of Islamic knowledge. This paper highlights a number of problems related to the underlying hypotheses as well as the relevant methodologies. It attempts to provide an Islamic view on the classification of knowledge in relation to the Islamisation project. Special reference is made to the dimensions of Islamisation in Psychology as a case study and its implications for the disciplines of Fiqh and Usul al-Fiqh. The authors conclude that Islamisation of the human sciences cannot be carried out without wider changes in the societal framework.